Sistem Pendukung Keputusan Penerima Bantuan Langsung Tunai Dana Desa di Pekandangan Menggunakan Metode AHP-TOPSIS - Habibah, Umu; Rosyda, Miftahurrahma (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Government efforts to reduce the burden on the community indonesia poor affected by providing aid covid-19 the cash that is a source of the funds from the village or commonly called cash transfer village funds (BLT-DD). The distribution of blt-dd this needs to be done quickly and directed. But in the election of a candidate BLT-DD recipients this are still being undertaken in an unconventional manner so that , the determination of certification BLT-DD recipients to less than optimal. The purpose of this research was a concept to build the system with applies the methods of analitycal hierarchy processes (AHP) - technique for order preference by similarity to ideal solution (TOPSIS) in the determination of the communities in receipt of BLT-DD that can help the village administration Pekandangan in choosing recipients BLT-DD. Criteria used is 3 criteria that is the community who were not currently other social help PKH ( Program Keluarga Harapan ) / the cards pre workings etc, jobs / reserve enough of financial three months fore, and has family members and sick or chronic perennials. eight priority was obtained from the calculation on to the method AHP and used in seeking value matrix normalization terbobot to the method TOPSIS. Testing the accuracy of this research using confusion matrix , and the results of 91 % accuracy. Ranking it produces the research data alternative pekandangan village used by government for consideration decision making in choosing BLT-DD recipients.